Synergistic Anti-Inflammatory Activity of Apolipoprotein A-I and CIGB-258 in Reconstituted High-Density Lipoproteins (rHDL) against Acute Toxicity of Carboxymethyllysine in Zebrafish and Its Embryo - Kyung-Hyun Cho; Ji-Eun Kim; Dae-Jin Kang; Maria del Carmen Dominguez-Horta; Gillian Martinez-Donato (MDPI AG, 2024)
CIGB-258 is a 3 kDa altered peptide ligand from heat shock protein (HSP) 60 that exhibits anti-inflammatory activity against the acute toxicity of carboxymethyllysine (CML) with antioxidant and anti-glycation activities via protection of high-density lipoprotein (HDL) and apolipoprotein A-I (apoA-I). It is necessary to test a synergistic interaction between apoA-I and CIGB-258 in reconstituted high-density lipoproteins (rHDL). Several rHDLs were synthesized containing palmitoyloleoyl phosphatidylcholine (POPC), cholesterol, apoA-I, and CIGB-258 at molar ratios of 95:5:1:0, 95:5:1:0.1, 95:5:1:0.5, and 95:5:1:1 for rHDL-(1:0), rHDL-(1:0.1), rHDL-(1:0.5), and rHDL-(1:1), respectively. As the CIGB-258 content in rHDL was increased, the particle size of rHDL was 1.4-times higher than rHDL-(1:0) to rHDL-(1:1), from 60 nm to 83 nm, respectively. As the CIGB-258 content was increased, the rHDL showed the most resistance to isothermal denaturation by a urea treatment, and rHDL-(1:1) exhibited the highest structural stability and the strongest antioxidant ability against LDL oxidation. Co-treatment of rHDL-(1:0), rHDL-(1:0.5), and rHDL-(1:1) resulted in up to 10%, 24%, and 34% inhibition of HDL glycation, inhibition of HDL glycation, which was caused by the CML, with protection of apoA-I. Microinjection of each rHDL into zebrafish embryos in the presence of CML showed that a higher CIGB-258 content in rHDL was associated with higher survivability with the least inflammation and apoptosis. Furthermore, an intraperitoneal injection of rHDL and CML showed that a higher CIGB-258 content in rHDL was also associated with higher survivability of zebrafish and faster recovery of swimming ability. The rHDL-(1:1) group showed the lowest triglyceride, AST, and ALT serum levels with the least production of interleukin-6, oxidized product, and neutrophil infiltration in hepatic tissue. In conclusion, CIGB-258 could bind well to phospholipids and cholesterol to stabilize apoA-I in the rHDL structure against denaturation stress and larger particle sizes. The rHDL containing CIGB-258 enhanced the in vitro antioxidant ability against LDL oxidation, the anti-glycation activity to protect HDL, and the in vivo anti-inflammatory activity against CML toxicity in zebrafish adults and embryos. Overall, incorporating apoA-I and CIGB-258 in rHDL resulted in a synergistic interaction to enhance the structural and functional correlations in a dose-dependent manner of CIGB-258.